2019
DOI: 10.1002/fsn3.1156
|View full text |Cite
|
Sign up to set email alerts
|

Porcine placental extract facilitates memory and learning in aged mice

Abstract: Aging induces a decline in both memory and learning ability without predisposing an individual to diseases of the central nervous system, such as dementia. This decline can have a variety of adverse effects on daily life, and it can also gradually affect the individual and the people they are surrounded by. Since recent evidence indicated that placental extract has effects on brain function such as memory, we hypothesized that placental extract could ameliorate the age‐associated reduction in cognitive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Previous studies of porcine placental extract showed that doses of 242 and 2424 mg/kg/day extract were administered via gavage to 5XFAD mice [ 3 ]. Another study on porcine placental extract in aged mice indicated that the effective doses of the extract were 1000 and 5000 mg/kg/day [ 2 ]. Therefore, we set the feeding doses for the present study as 0.03% and 3%, which are almost equal to 50 mg/kg/day and 5000 mg/kg/day, respectively, because the average daily feeding amount was 5 g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of porcine placental extract showed that doses of 242 and 2424 mg/kg/day extract were administered via gavage to 5XFAD mice [ 3 ]. Another study on porcine placental extract in aged mice indicated that the effective doses of the extract were 1000 and 5000 mg/kg/day [ 2 ]. Therefore, we set the feeding doses for the present study as 0.03% and 3%, which are almost equal to 50 mg/kg/day and 5000 mg/kg/day, respectively, because the average daily feeding amount was 5 g.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report on porcine placental extract in chronically stressed and ovariectomized mice demonstrated protection against a decline in neuronal number in the hippocampal CA3 region [ 1 ]. Another study using porcine placental extract showed no change in neuronal numbers in the hippocampus after extract treatment in aged mice, although memory deficits were recovered [ 2 ]. These previous reports suggest a neuroprotective effect of the placental extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nissl staining is often used to detect the activity of neurons and impairment of neurons would lead to the reduction of Nissl bodies ( 41 , 42 ). A small amount of Nissl positive cells was found in the hippocampus of rats underwent MS as well as CUMS.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from ARPE-19 cells using TRI Reagent (TR118, MRC, OH, USA) and cDNA was synthesized using the PrimeScript RT reagent Kit with gDNA Eraser (Takara Bio Inc., Japan). qPCR was performed as previously described [ 16 ]. The primer sequences are listed in Additional file 1 : Table S1.…”
Section: Main Textmentioning
confidence: 99%